Research on Pump Volute Design Method Using CFD - Sunsheng Yang; Fanyu Kong; Bin Chen (International Journal of Rotating Machinery)
Volute is an important hydraulic part of centrifugal pump, hydraulic loss within pump volute takes up a large part of total hydraulic loss within pump, thus appropriate design of pump volute has significant meaning to centrifugal pump performance. In this paper, numerical method was adopted to investigate volute main geometric parameters, including volute throat area, volute cross-section shape, design rule of spiral development area, and radial gap between impeller and volute tongue to pump performance. A design method of high-efficiency pump volute is developed through the influence of volute main geometric parameters to pump performance. This paper could provide theoretical guidance to high-efficiency pump volute design.